Molecular docking, in-silico ADMET screening, MM-GBSA binding free energy of some novel isoxazole substituted 9-amnoacridines as HER2 inhibitors targetting breast cancer. (10th May 2020) - Kalirajan, Rajagopal; Pandiselvi, A.; Gowramma, B.
9-Aminoacridines are known DNA-intercalating agents, due to antiproliferative properties. Anticancer agents with 9-aminoacridines like amascrine, and nitracrine were developed. Docking studies were performed for isoxazole substituted 9-aminoacridines 1a-x as selective HER2 inhibitors (PDB id-3PP0) targeting breast cancer using Schrodinger suit-2016-2, Maestro 9.6 version. Docking against HER2 was performed using Glide module, Insilco ADMET screening by qikprop module and free binding energy by Prime- MMGBSA module. The binding affinity of the molecules towards HER2 was selected by GLIDE score and interaction patterns. Many compounds showed strong hydrophobic interactions and hydrogen bonding interactions to inhibit HER2. The compounds 1a-x have good binding affinity with Glide scores -6.6 to -9.7 when compared with standards ledacrine(-6.3) and tamoxifen(-3.7). The ADMET properties are within recommended values. MM-GBSA binding results of the most potent inhibitor are favourable. The compounds, 1o, f, n, d, m, w with good Glide scores may produce significant anti-breast cancer activity and further in-vitro and in-vivo investigations.